Interactions between microfibrillar cellulose and carboxymethyl cellulose in an aqueous suspension - Agarwal, Deepa; Macnaughtan, William; Foster, Tim (Elsevier, 2018)
New microstructures with interesting, unique and stable textures, particularly relevant to food systems were created by redispersing Microfibrillar cellulose (MFC). This paper reports the interactions between microfibrillar cellulose and carboxymethyl cellulose (CMC) in redispersed aqueous suspensions, by using rheological measurements on variable ratios of MFC/CMC and correlating these with apparent water mobility as determined by time domain NMR. MFC is a network of cellulose fibrils produced by subjecting pure cellulose pulp to high-pressure mechanical homogenisation. A charged polymer such as CMC reduces the aggregation of microfibrillar/fibre bundles upon drying. Small amplitude oscillatory rheological analysis showed the viscoelastic gel-like behaviour of suspensions which was independent of the CMC content in the MFC suspension. A viscous synergistic effect was observed when CMC was added to MFC before drying, leading to improved redispersibility of the suspension. Novel measurements of NMR relaxation suggested that the aggregated microfibrillar/fibre bundles normally dominate the relaxation times (T2). The dense microfibrillar network plays an important role in generating stable rheological properties and controlling the mobility of the polymer and hence the apparent mobility of the water in the suspensions.